2017
DOI: 10.1089/chi.2016.0233
|View full text |Cite
|
Sign up to set email alerts
|

Two Pilot Randomized Trials To Examine Feasibility and Impact of Treated Parents as Peer Interventionists in Family-Based Pediatric Weight Management

Abstract: Two pilot randomized clinical trials suggest parents-as-peer interventionists in FBT may be feasible, efficacious, and delivered at lower costs, with perhaps some additional benefits to serving as a peer interventionist. More robust investigation is warranted of peer treatment delivery models for pediatric weight management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…107 Finally, one study targeting students in low SES neighborhoods found an online intervention more cost-effective than the onsite version. 79 [143][144][145][146][147][148][149]151,[153][154][155][156][157][163][164][165][166]168,169,[173][174][175][176][177][178][179][180] One intervention included the use of a mobile health technology (m-health) component to target addictive eating behavior. 171 Five were bariatric surgery interventions.…”
Section: Key Cost-effectiveness Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…107 Finally, one study targeting students in low SES neighborhoods found an online intervention more cost-effective than the onsite version. 79 [143][144][145][146][147][148][149]151,[153][154][155][156][157][163][164][165][166]168,169,[173][174][175][176][177][178][179][180] One intervention included the use of a mobile health technology (m-health) component to target addictive eating behavior. 171 Five were bariatric surgery interventions.…”
Section: Key Cost-effectiveness Resultsmentioning
confidence: 99%
“…Like prevention-only interventions, the settings were more likely to be healthcare based [148][149][150]158,159,161,163,167,170 or in the home alongside family members. [143][144][145][146]151,157,166,173 Generally, treatment-only interventions were likely to be cost-effective in the long run.…”
Section: Key Cost-effectiveness Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After the exclusion of the duplicates in the databases, the screening and eligibility criteria were applied. Finally, 29 articles were included for data synthesis in this review [ 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 ].…”
Section: Resultsmentioning
confidence: 99%
“…We followed-up with eligible parents via phone or email; 23 parents (11 TEP and 12 TNP) enrolled in the study. To capture a range of experiences and preferences, we purposefully recruited TEP participants who had previously participated in one of four different treatment programs, specific characteristics of which are described elsewhere ( Nutrition and Fitness for Life, 2017 ; Saelens et al, 2017 ). Recruitment stopped when no new pertinent concepts were found, and thus thematic saturation was reached ( Guest et al, 2006 ; Patton, 2002 ).…”
Section: Methodsmentioning
confidence: 99%